DAMPAK IRIGASI TERHADAP PENDAPATAN USAHATANI PADI SAWAH SETELAH LIKUIFAKSI DI DESA SIBALAYA UTARA KECAMATAN TANAMBULAVA KABUPATEN SIGI - Muhamad Fahrul; Dafina Howara; Erny Sirappa (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
This research aimed to determine the impact of irrigation on lowland rice farming income post-liquefaction in Sibalaya Utara village Tanambulava sub district of Sigi district. The respondents were selected by Purposive Sampling method from a population of 201 rice farmers in Sibalaya Utara village. The analysis used was Multiple Linear Regression analysis. The results showed that the income of the lowland rice farming before being affected by the liquefaction was significantly greater (IDR 9,673,807/ha) than that after the liquefaction (IDR 1,713,982/ha) in Sibalaya Utara Village, Tanambulava District, Sigi Regency. This was mostly caused by the severely damaged irrigation infrastructure in the liquefaction area, which left the lowland rice-growing region with virtually little water supplies.